2011
DOI: 10.1007/s12028-010-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lacosamide in Refractory Status Epilepticus

Abstract: This is the largest case series to date describing the use of lacosamide in patients with RSE. Despite the novel mechanism of action, we observed no evidence that lacosamide is effective in RSE; however, our sample size was small. Further study is needed to determine the role of lacosamide in SE, especially early in the treatment course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 9 publications
0
54
0
2
Order By: Relevance
“…This is in contrast to the other studies/case reports discussed here, where patients could have received lacosamide as a first-line AED, and in fact, 20.8 % of the patients in our study did so. Minor adverse events were noted in this trial [22], although only one allergic skin reaction was clearly associated with intravenous lacosamide and three of the nine patients reported angioedema with lacosamide leading to discontinuation in one patient [22]. In the systematic review of case reports and case series in 136 patients with SE, the overall rate of adverse events was low and the most common was mild sedation in 25 cases.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This is in contrast to the other studies/case reports discussed here, where patients could have received lacosamide as a first-line AED, and in fact, 20.8 % of the patients in our study did so. Minor adverse events were noted in this trial [22], although only one allergic skin reaction was clearly associated with intravenous lacosamide and three of the nine patients reported angioedema with lacosamide leading to discontinuation in one patient [22]. In the systematic review of case reports and case series in 136 patients with SE, the overall rate of adverse events was low and the most common was mild sedation in 25 cases.…”
Section: Discussionmentioning
confidence: 72%
“…The reasons underlying this lack of response to lacosamide in the Goodwin et al study is unclear, but are likely due to small patient numbers and the use of the agent as at least a third-line therapy in known refractory patients. In the Goodwin trial, the most frequently used regimen of intravenous lacosamide was a 200 mg initial dose, followed by 200 mg every 12 h [22]. This is similar to the dose used in the current trial (400 mg/day for 8 days), perhaps negating the suggestion that patients were under dosed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1 In animal models, its utility to reduce the cumilative seizure time of self-sustaining status epilepticus and hippocampal neuronal damage was shown. 2 In 3 randomized doubleblind, placebo-controlled, multicenter trials in more than 1200 patients, efficiency of LCM was studied and they reported a significant reduction in seizure frequency with doses of 200 to 600 mg/d. [3][4][5] Additionally, as a result of new clinical studies on status epilepticus (SE), LCM remarked compared with other new antiepileptic drugs (AED).…”
Section: Letter To the Editormentioning
confidence: 99%
“…[202122] However, a small case series at Johns Hopkins hospital did not find significant difference in outcomes with use of lacosamide. [23]…”
Section: Introductionmentioning
confidence: 99%